A Comprehensive Study on Concurrent Engineering (International Journal of Food and Nutritional Sciences, 2022)
Concurrent engineering, often known as simultaneous engineering, is a products development method in which the different stages are completed simultaneously rather than sequentially. It cuts the time it takes to create a product and bring it to market, leading in higher production and cheaper costs. The industrialization has reached its saturation point due to design and manufacturing engineering. Due to increasing industrial expansion and market needs, millions of items are manufactured every day throughout the globe. In order to meet demand, the input and output rates must be equal on a broad scale. Alternative solutions are required to enhance production rates with more efficiency and in less time. Concurrent Engineering allows for increased production rates, better quality, and shorter lead times. Achieving sustainable business operations while keeping the environment in mind is also critical for any organization's long-term survival and profit while reducing negative environmental consequences. It is the development of a product and a process at the same time. This study’s major focus is the formation of cross-functional teams. Concurrent engineering's efficacy in industrial processes and the environment has been shown. In the future, Concurrent Engineering is a product development technique in which all activities and tasks are carried out concurrently.